Assessing Nursing Staff Knowledge and management in Radiation Protection - Bandar Ali Alasmari, Abdullah Ibrahim Alshudayyid, Reem Musaddif Nahari, Abdlmageed Ibrahim Al-Shdaid, Latifah Abdullah Alshahrani, Faleh Nafea Alshammari (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Exposure to radiation among nursing staff, though typically below established limits for radiation workers, remains a concern due to its potential impact on routine activities in specific hospital departments. Moreover, nursing staff, regardless of their classification as radiation workers, must be equipped to respond to radiological emergencies and provide care to patients affected by radiation. Despite this imperative, there is a gap in understanding the extent of awareness and preparedness among nursing staff regarding radiation safety. This study seeks to address this gap by assessing the level of radiation safety awareness among nursing staff in various departments of a major hospital. Methods: A prospective study was conducted involving 200 nurses across nine different departments of the hospital. A structured multiple-choice questionnaire, designed to evaluate knowledge typically covered in basic radiation safety courses, was distributed to the participants. The questionnaire aimed to gauge the level of awareness and understanding of radiation safety principles among nursing staff. Participation was voluntary, and responses were anonymized to ensure confidentiality. Data analysis involved examining the average score achieved by participants and assessing their perceptions regarding the need for further radiation safety training in their respective departments. Results: Of the 200 nurses approached, 147 (74%) completed the questionnaire. The analysis revealed an average score of 40% among participants, indicating varying levels of knowledge regarding radiation safety principles. Furthermore, 85% of surveyed nurses expressed a perceived need for additional radiation safety training within their departments to support their daily activities. These findings underscore the importance of addressing gaps in radiation safety knowledge among nursing staff and implementing targeted training programs to enhance preparedness. Conclusion: The study highlights significant gaps in radiation safety awareness among nursing staff in the hospital’s various departments. The findings emphasize the importance of providing tailored radiation safety training to nursing staff, considering their specific departmental responsibilities and potential exposure risks. It is imperative to prioritize ongoing education and training initiatives to ensure nursing staff are adequately prepared to mitigate radiation-related risks and respond effectively to radiological emergencies. By addressing these gaps in knowledge and practice, healthcare facilities can enhance the safety and well-being of both patients and nursing staff.